Relación entre la recaudación tributaria y las micro y pequeñas empresas registradas en la Municipalidad Provincial de Maynas durante el periodo 2007–2021 - Zumaeta Cahuaza, Isaac (2025)
The analysis of the relationship between tax collection and micro and small businesses (MYPE) registered in the Provincial Municipality of Maynas during the period 2007-2021 reveals a significant positive compensation. As the number of registered MSEs has increased, so has tax collection. This suggests that the formalization and growth of these companies contribute substantially to local tax revenues. The regressions carried out confirm the robustness of this relationship, highlighting that the simplification of procedures, the promotion of tax culture and tax incentives are essential to maintain and enhance this positive effect. Tax collection shows a growing trend, reflecting improvements in tax management and a favorable economic environment. The number of MYPEs has also grown steadily, indicating a favorable environment for the creation and formalization of businesses. Strengthening tax administration, continuous support for MSEs, and comprehensive local development policies are essential to maximize the economic benefits of this relationship.